Growth, structure, electrical and optical properties of transition metal chalcogenide crystals synthesized by improved chemical vapor transport technique for semiconductor technologies. Issue 3 (August 2022) - Dasadia, Abhay; Bhavsar, Vidhi
Abstract: Low dimensional structures, including bulk crystals, thin films, nanowires and nanotubes, have received remarkable attention due to their novel functionality and potential applications in various areas of optics, electronics, photonics, and sensing devices and photovoltaic field. Recently, remarkable progress and modification have been achieved in the synthesis process of crystalline material by vapor transport technique. In this review, we introduce an improved concept of the closed tube Chemical Vapor Transport (CVT) technique for the single crystal growth of ZrSTe, TiSTe and TiSeTe. A modified reverse temperature profile has reported the growth of ZrSTe, TiSTe and TiSeTe results show the good crystalline quality of synthesized materials. The single-crystal X-ray diffraction data reveals all three samples have trigonal unit cell structure with a space group of P31. The Semiconducting behavior of grown crystals of ZrSTe, TiSTe and TiSeTe was verified by two probe resistivity measurements, Hall Effect measurements and optical absorption at room temperature in the spectral range of 200 nm - 2200 nm. In this review, we highlight the recent progress in the transition of metal chalcogenides for their advanced application in solar energy conversion, thin-film electronics, optoelectronic devices and quantum communication devices. Moreover, different experimental challenges within the described growth technique are probed. Additionally, a survey was done for the possible enhancement of Transition Metal Chalcogenide (TMC) crystalline materials grown by the Chemical Vapor Transport technique based on various growth parameters.